2010
DOI: 10.1016/j.ejcts.2009.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a new chest tube removal protocol using digital air leak monitoring after lobectomy: a prospective randomised trial

Abstract: The application of a chest tube removal protocol using a digital drainage unit featuring a continuous recording of air leak was safe and cost effective. Although future studies are warranted to confirm these results in other settings, the use of this new protocol is now routinely applied in our practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
109
1
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(115 citation statements)
references
References 18 publications
2
109
1
3
Order By: Relevance
“…Recently digital drainage systems have been developed and these systems facilitate the patients to ambulate without attached to wall suction and also make it easy for physicians to decide when to remove tubes objectively (1). Digital monitoring systems reduced hospital stay and medical expenses (2,3). But with these advantages over traditional drainage systems, physicians still visit the patients to confirm the state of chest drainage systems.…”
Section: Introductionmentioning
confidence: 99%
“…Recently digital drainage systems have been developed and these systems facilitate the patients to ambulate without attached to wall suction and also make it easy for physicians to decide when to remove tubes objectively (1). Digital monitoring systems reduced hospital stay and medical expenses (2,3). But with these advantages over traditional drainage systems, physicians still visit the patients to confirm the state of chest drainage systems.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] To date, two randomized studies have shown that DCS was superior to ACS in terms of chest tube management. 6,7) The Thopaz DCS (Medela, Baar, Switzerland) has a screen that displays instantaneous values for pleural pressure and PAL rate, allowing objective, real-time, quantitative assessment of PAL via the chest tube. Data are also recorded continuously and presented as a graph of the PAL over the preceding 24h.…”
mentioning
confidence: 99%
“…To date, drainage systems have only been compared with relation to postoperative air leak (11)(12)(13)(14)(15). Whilst this is an important aspect of the decision to remove chest tubes, the volume of fluid extracted is another major determinant, that continues to garner increased attention amongst research circles (2,(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…Our trial attempts to evaluate whether intermittent (as opposed to traditional continuous) controlled suctioning provided via the mechanism of digital drainage decreases pleural irritation and inflammation and therefore decreases the amount of pleural drainage. Previously published reports have demonstrated that digital drainage systems are superior in reducing the incidence of post-operative prolonged air leak (12)(13)(14). Several articles describe the advantage of a digital system in eliminating the inter-observer differences related to air leak grading, as the system quantifies the precise amount of air leak (13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation